The Use of Discriminatory Function on the Early Expectation of Corporate Financial Bankruptcy: Listed Firms on the Tehran Stock Exchange. - Faysal, Saad Raad (International Journal of Scientific Research and Management (IJSRM), 2023)
The purpose of this paper is to investigate the accuracy of the discriminant function in the process of predicted financial failure before it occurs. Using the economic definition (profit and loss) and on this basis, the companies have been classified as a failure and Non-failure for three consecutive years. This paper also tries to discover when bankruptcy phenomenon. Therefore, the multi-step analysis was used to achieve this purpose to shed more light on the validity of the discriminant function in the forecasting process with different locations and different economic sectors except for the financial sector of the listed firms in Tehran Stock Exchange during 2016-2018 with the companies traded 101 companies classified to 11 failure companies And 90 non-failure companies with 25 ratios listed under the title of liquidity, solvency, activity and profitability, and comparing the results for three years. In the end, this paper found the success of The Discriminant function in predicting financial failure for all years of study, In other markets to predict financial position. The sample belonging to the Tehran Stock Exchange (TSE) showed that the financial ratios affecting the formation of the legal discriminatory function (model) were different from year to year. The final financial position of companies that lost three consecutive years was also explained by comparison with 2019, Bankruptcy phenomenon of 64% of financially failed companies (losers).